Foreign direct investment in Central Eastern Europe: Some lessons for Poland from Hungary - Csilla Hany (Intereconomics, 1995)
Foreign direct investment (FDI) has a significant role to play not only in the process of accelerating privatization, but in the development and strengthening of the emerging market economies of Central Eastern Europe (CEE). The inflow of FDI into Poland up to 1994 was marginal as compared to Hungary and the Czech Republic. The following paper examines the situation in Poland and outlines what lessons can be learnt from the Hungarian experience.
Keywords: 330; System Transformation